Reproducibility of nuclear morphometry parameters from cytologic smears of canine cutaneous mast cell tumors--intra- and interobserver variability - Barbosa, Daniella de F L (Veterinary clinical pathology, 2014)
© 2014 American Society for Veterinary Clinical Pathology and European Society for Veterinary Clinical Pathology.